2004
DOI: 10.1159/000096801
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical and Corticothalamic Interaction in the Auditory System

Abstract: The neuronal interconnections between thalamus and cortex modulate information transmission in the central auditory system. To facilitate the understanding of its modulation effects and mechanism, first, the recent progress on investigating the anatomical connections and the physiological properties of the medial geniculate body and auditory cortex is summarized. Second, the connectional pattern and functional organization in thalamocortical and corticothalamic network are described. Third, the strategic posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 136 publications
2
3
0
Order By: Relevance
“…5) were generally consistent with current understanding of cortical auditory processing. Our results are consistent with the hypothesis that thalamo-cortical projections transmit auditory information from the thalamus to early auditory cortex, from where cortico-cortical projections relay the results to other perisylvian areas to extract complex auditory features (Zhang et al, 2004; Kumar et al, 2007; Zatorre et al, 2007). Specifically, previous studies have shown that neurons in the medial geniculate nucleus of the thalamus send auditory information to the cortex through projections that terminate in primary auditory cortex (Steriade et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5) were generally consistent with current understanding of cortical auditory processing. Our results are consistent with the hypothesis that thalamo-cortical projections transmit auditory information from the thalamus to early auditory cortex, from where cortico-cortical projections relay the results to other perisylvian areas to extract complex auditory features (Zhang et al, 2004; Kumar et al, 2007; Zatorre et al, 2007). Specifically, previous studies have shown that neurons in the medial geniculate nucleus of the thalamus send auditory information to the cortex through projections that terminate in primary auditory cortex (Steriade et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…These processes include ECoG modulations in the alpha (8-12 Hz) and high gamma (70-110 Hz) frequency bands. Activity in the alpha band seems to reflect interactions between the thalamus and the cortex (Steriade et al, 1990; Lopes Da Silva, 1991; Zhang et al, 2004), and may facilitate information transfer to task-related cortical areas by inhibiting neural activity in task-unrelated areas (Jensen and Mazaheri, 2010). On the other hand, activity in the high gamma band seems to reflect task-related activity of neural populations directly underneath the electrodes (Crone et al, 1998; Miller et al, 2007, 2009; Schalk et al, 2007; Crone et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results suggest that thalamo- (Zhang et al, 2004;Kumar 266 et al, 2007;Zatorre et al, 2007) (see illustrative yel-267 low arrows in Fig. 4c).…”
supporting
confidence: 66%
“…Activity in the alpha band is thought to represent 62 thalamo-cortical interactions(Steriade et al, 1990; 63 daSilva, 1991;Zhang et al, 2004), whereas activ-64 ity in the high gamma band is believed to index the 65 activity of local population of neurons(Miller et al, 66 2009;Miller, 2010). To extract the time course of al-67 pha and high gamma activity, we filtered ECoG sig-68 nals from each electrode at each specific frequency 69 band using an IIR band-pass filter, and removed spatial 70 noise common to all ECoG electrodes using a com-71 mon average reference (CAR) spatial filter.…”
mentioning
confidence: 99%
“…The primary and non-primary modules receive unimodal and polymodal sensory inputs, respectively, whereas the association module can integrate sensory inputs of multiple modalities with information related to animal's behavioral states 7,10 . These three modules of sensory thalamus project to the cortex largely in a topographical manner, that is, they preferentially project to the middle layers of the primary, secondary and association sensory cortices 7,[11][12][13] , respectively, although the non-primary and association thalamic neurons may also have axons fibers that extend horizontally in the superficial layer to other cortical areas 7,9,[13][14][15] . These topographically organized thalamocortical pathways serve as essential conduits for sensory integration, perception, and the construction of our conscious experience of the world around us.…”
Section: Introductionmentioning
confidence: 99%